RESOURCES OF ATTITUDES IN STUDENTS’ TOURISM BLOGS - Ni Putu Era Marsakawati; Rima Andriani Sari; Putu Dewi Merlyna Yuda Pramesti; Komang Windi Wahana Putra (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2021)
Studies concerning the use of attitude resources in students’ writing have been conducted by researchers. However, limited attention has been given to investigate how resources of attitude are used in a hybrid genre, such as blog. This paper aims at reporting how attitude resources are realized in students’ tourism blogs. 10 tourism blogs written by the seventh-semester students of English Education Department, taking English for Tourism course were purposively selected as the source of data. These data were chosen because their topics were about tourist attractions in Bali. The data were analyzed by following appraisal language analysis theory. The results show that appreciation and affect resources were used by the students in their blogs. However, the resources used by the students were basic and repetitive words. This study suggests English instructors provide explicit teaching of attitudinal words that the students can use when they are writing tourism blogs.